Distribution of Motor Vehicle Volumes and Ambient Air Dust Levels in Hot Points of Yogyakarta City, Indonesia - Ardianto, Heru; Dyah Prasetyawati, Naris; Sudaryanto, Sigid (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Yogyakarta City, Indonesia is a center for tourism, government, education, and the economy. In line with increasing mobility and transportation, this situation has a positive impact economically, but a negative impact in terms of air pollution due to vehicle emissions. Motorized vehicles contribute to air pollution reaching 66.34% of total pollution. PM2.5 is a critical parameter in the city of Yogyakarta. Methods: This research aims to determine the volume of motorized vehicle traffic and the distribution of dust levels in the ambient air of Yogyakarta City. Data collection used non-probability purposive sampling with the roadside method. Vehicle volume is mapped using hotspots and dust levels using interpolation. Results and Discussion: The average vehicle volume in the morning was 2,293.147 pcu/hour and in the afternoon it was 2,301.173 pcu/hour. The hotspot results showed that the volume of motorized vehicles in the morning category was very high at 2,921.600-5,655 pcu/hour and in the afternoon it was 3,678.800-4,558 pcu/hour. The average dust content in the morning is 0.10667 grams/m3 and in the afternoon it is 0.10240 grams/m3. The interpolation results showed that the distribution of dust levels in the very high category in the morning was 0.17000-0.20000 grams/m3 and in the afternoon it was 0.21000-0.26000 grams/m3. Conclusion: The highest average volume of vehicles occurs in the afternoon while the highest total dust content occurs in the morning.